PENGAPLIKASIAN MODEL BLENDED LEARNING PADA PERANGKAT PEMBELAJARAN BAHASA INDONESIA - Hanniza Karini (Universitas Negeri Medan, 2019)
Abstract This research is a research and development that aims to apply the Scientific Blended Learning (SBL) learning model through the development of valid, practical and effective SBL learning tools. Learning tools developed include: (1) Learning Implementation Plan (RPP); (2) Student Worksheets (LKS) (3) Handbook for Edodo Use; and (4) Content / contents of Edmodo virtual classroom facilities. The stages of development include four 4-D stages which are modified into 3 stages: defining, designing, and developing. Keywords: Scientific Blended Learning, Learning Tool